Penerapan Teknologi Produksi Permen Kopi di Kecamatan Sungai Bungkal Kota Sungai Penuh Jambi - Mursalin Mursalin; Sutrisno Sutrisno; Jodion Siburian; Bayu Rosadi; Guspianto Guspianto (Jurnal Nusantara Mengabdi, 2023)
Purpose: This activity is intended to introduce coffee processing techniques into coffee candy by way of counseling, training and mentoring to the coffee farmer groups in Sungai Penuh City, Jambi. Methodology: The stages of this activity include counseling, training, production demonstrations, and business assistance. Coffee candy is made by boiling a mixture of coffee extract, sucrose and glucose at a ratio of 13:8:6 until it boils. After the mixture thickens, reduce the stove heat until the temperature of the mixture is no more than 1100C. After crystallization is complete, the mixture is put into the mold, cooled, then the coffee candy is removed from the mold, wrapped in plastic and packaged. Result: Counseling, training, mentoring, and technical guidance on how to process ground coffee into coffee candy have succeeded in creating a new source of income for the people of Sungai Ning Village, Sungai Bungkal District, Sungai Penuh City, Jambi. Conclusion: Through this activity, the village community has been able to apply coffee candy manufacturing technology as an effort to diversify their processed coffee products, coffee candy has now become their mainstay commodity, and several assisted farmer groups have now started producing coffee candy and marketing their products at every opportunity.